Non descend vaginal hysterectomy (NDVH) for benign gynecological conditions - Nusee, Zalina (2019)
The most common indications for vaginal (VH) hysterectomy in United State (Whiteman MK, 2018) are symptomatic uterine leiomyomas (51.4%), abnormal uterine bleeding (41.7%), endometriosis (30%) and prolapse (18.2%). The American College of Obstetricians and Gynecologists (ACOG 2017) makes recommendations that VH is the approach of choice whenever feasible. The Cochrane systematic review on 47 studies concluded that VH has the best outcomes compare to abdominal and laparoscopic route. The vaginal approach is the natural route of excellence, which called “natural orifice hysterectomy” or “no scar hysterectomy” which seem to be the current trend for the minimally invasive context. VH is a long-practiced procedure since fourteen century (Berengario de Carpi, 1470–1550), which follow all the criteria of minimally invasive gynecology surgery. However, it is difficult to explain why vaginal hysterectomy, does not hold a preferential place among surgeons. Advantages of the vaginal route includes less surgical time, closing of abdominal wall is not required therefore no post operative wound complications. The incidences of post-operative paralitic ileums, flatulence and adherences is diminished due to minimal peritoneal incision and handling of intestines. Post-operative recovery is less painful and faster. Compare to laparoscopy, it does not requires general anesthesia, faster learning curve and has less risk of ureteric injury. VH requires less  sophisticated instruments and logistics therefore it involved very minimal cost. The literature clearly reveals that VH can be accomplished in 94–99% of cases with the absence of uterine prolapse. Surprisingly  for years majority of surgeons have classified vaginal hysterectomy as a procedure limited to uterine prolapse. This reflects the ignorance of many concerning the world literature and a typical example of those treatments considered unprofitable for the industry that have therefore not gained adequate support. The conditions that lead surgeons to believe that the vaginal route is not a suitable option includes: no prolapse, big uterus, history of cesarean or pelvic surgery, nullipara or no vaginal delivery and the patient needs an oophorectomy. The fact that these are just simple myths must be pointed out. It is actually the surgeon’s experience and skills that will play the decisive role.